Iowa Birdline update, November 20, 1989, part two - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for November 20, 1989. Highlights include a White-winged Crossbill invasion with several reports coming in of sightings across the state. Epson - sheet feed/flatbed